The Study of Factors Which Related to Continuous Outpatient Addiction Treatment in Matrix Program, Chon Buri - Thamkittikhun, Nuannoy (Journal of Health Science of Thailand, 2018)
The objective of this study was to determine relation and to predict behavior of patients who could accomplish continuous outpatient addiction treatment in Matrix program in public health sector, Chon Buri. The samples were 250 outpatients, completely finished addiction treatment program within 1 year ,were recruited by simple random. These patients completed questionnaires between January and April 2006. The statistic methods that used in this survey were frequency, percentage, chi square test, Pearsonีs production moment correlation coefficient and multiple regression analysis. The result showed that only 53 percent patients who finished this program. Biosocial factors that related to continuous participation in this treatment program were age, education, status, income and reasons to participate to this program. While psycho factors were knowledge, attitude, future goal, and self control and belief. Social factors which related to fulfill this treatment program were friends, families and health care alliesี support. Thus, factors that can be used to predict the completion of this program were 3 factors (future goal orientation and self-control, friends support, and families support). The equation that can be used to predict the possibility to fulfill this program is as follows: Z = 0.48 (future goal orientation and self-control) + 0.33 (friends support) +0.12 (families support)